2005
DOI: 10.2135/cropsci2004.0567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Soil Moisture Status during Seed Development on Soybean Seed Isoflavone Concentration and Composition

Abstract: Soybean [Glycine max (L.) Merr.] seed isoflavone concentration 1999). Studies with humans (Crouse et al., 1999) and has been shown to be highly dependent on environmental conditions, monkeys (Anthony et al., 1997) show that isoflavonebut isoflavone concentrations have not been studied under controlled conditions to quantify the effects of specific factors. To determine rich soy protein isolates are more effective than purified the effect of air temperature and soil moisture status during soybean isoflavones fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
98
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(124 citation statements)
references
References 18 publications
19
98
1
6
Order By: Relevance
“…Generally, in this study, environments which were warmer and drier resulted in less seed isoflavone levels across all genotypes than those environments which were cooler and wetter, consistent with previous studies (Tsukamoto et al 1995;Caldwell et al 2005;Lozovaya et al 2005). Mean isoflavone level ranged from 1600 to 3700 mg g (1 across the 10 environments.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Generally, in this study, environments which were warmer and drier resulted in less seed isoflavone levels across all genotypes than those environments which were cooler and wetter, consistent with previous studies (Tsukamoto et al 1995;Caldwell et al 2005;Lozovaya et al 2005). Mean isoflavone level ranged from 1600 to 3700 mg g (1 across the 10 environments.…”
Section: Resultssupporting
confidence: 90%
“…This relationship is most likely a function of the relationship between temperature during seed fill and isoflavone accumulation. Cooler temperatures during the seed fill period increase isoflavone content (Caldwell et al 2005;Lozovaya et al 2005;Murphy 2007). The positive relationship between isoflavone content and maturity may be related to the timing of seed filling in later maturing lines, which occurs later in the season when temperatures can be expected to usually be lower in the Canadian soybean production regions.…”
Section: Resultsmentioning
confidence: 99%
“…Isoflavones accumulation over environments or their concentrations in plants varied widely (Hoeck et al, 2000;Mebrahtu, Mohamed, Wang, & Andebrhan, 2004;Caldwell, Britz, & Mirecki, 2005;Lozovaya, Lygin, Ulanov, Nelson, Dayde, & Widhohm, 2005) and generally plants are conducive to accumulate more isoflavone when growing in a controlled environment. This might due to desire well-watered and temperature condition.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers found that synthesis and accumulation of isoflavones were affected by irrigation, and irrigation increased isoflavones by 2.5 folds [66,67]. It was concluded that soil moisture increased daidzein, genistein and total isoflavones, but not glycitein when water stress was imposed at R6 [68]. Up to 45% increase of isoflavones was measured under irrigated conditions versus nonirrigated conditions [67].…”
Section: Isoflavonesmentioning
confidence: 91%